2021
DOI: 10.1111/obr.13227
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review of economic evaluations of web‐based or telephone‐delivered interventions for preventing overweight and obesity and/or improving obesity‐related behaviors

Abstract: Summary Obesity prevention interventions with behavioral or lifestyle‐related components delivered via web‐based or telephone technologies have been reported as comparatively low cost as compared with other intervention delivery modes, yet to date, no synthesized evidence of cost‐effectiveness has been published. This study aimed to conduct a systematic review of economic evaluations of obesity prevention interventions with a telehealth or eHealth intervention component. A systematic search of six academic dat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(23 citation statements)
references
References 82 publications
0
23
0
Order By: Relevance
“…Most previous systematic reviews about digital health interventions are limited to the self-management of clinical conditions or symptoms instead of focusing on health promotion [ 43 , 44 , 45 , 46 , 47 ] or try to understand only one major health outcome change such as nutrition-related behaviours [ 48 , 49 , 50 , 51 ], sedentary behaviours [ 52 ] and physical activity [ 53 ], depression and mental health [ 54 ], alcohol-related problems [ 55 ] and their target population is other than adolescents such as adults [ 56 ] and older adults [ 57 ].…”
Section: Discussionmentioning
confidence: 99%
“…Most previous systematic reviews about digital health interventions are limited to the self-management of clinical conditions or symptoms instead of focusing on health promotion [ 43 , 44 , 45 , 46 , 47 ] or try to understand only one major health outcome change such as nutrition-related behaviours [ 48 , 49 , 50 , 51 ], sedentary behaviours [ 52 ] and physical activity [ 53 ], depression and mental health [ 54 ], alcohol-related problems [ 55 ] and their target population is other than adolescents such as adults [ 56 ] and older adults [ 57 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have demonstrated that families who live further from clinics, or for whom travel to in-person appointments is more burdensome or complex, tend to view telemedicine more favorably [ 27 ]. Despite this, most published economic evaluations of telemedicine consider the perspectives of only the health care service/provider, as shown for cardiovascular disease management [ 28 ], obesity prevention [ 6 ], and eHealth more broadly [ 29 ]. It is important for researchers to assess delivery costs for future evaluations of digitally delivered pediatric weight management to build an evidence base for this population with unique care needs [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…For excess adiposity in childhood, family-orientated multidisciplinary weight management, consisting of nutrition and physical activity support with integration of evidence-based behavior-change techniques, is recommended as the cornerstone of treatment [ 2 - 4 ]. There is evidence that telemedicine interventions can support self-management of nutrition and physical activity in children and adolescents [ 5 ]; however, there is a scarcity of studies focusing on the economic evaluations of such interventions, particularly for mHealth interventions developed to incorporate evidence-based approaches [ 1 , 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, no rigorous trial has yet demonstrated the superiority of digital PA interventions over existing ones. Although e-health interventions are gaining popularity for the treatment of obesity, appearing advantageous compared with current programmes, no evidence of cost-effectiveness has been demonstrated 17. In addition, concerns remain regarding the adherence rate and engagement in the long term 18.…”
Section: Introductionmentioning
confidence: 99%
“…Although e-health interventions are gaining popularity for the treatment of obesity, appearing advantageous compared with current programmes, no evidence of cost-effectiveness has been demonstrated. 17 In addition, concerns remain regarding the adherence rate and engagement in the long term. 18 Therefore, the use of gamification appears as an interesting way to address these limits.…”
Section: Introductionmentioning
confidence: 99%